AB0030 INCREASED CIRCULATING CD19+CD24HICD38HI REGULATORY B CELLS ARE BIOMARKERS OF RESPONSE TO METHOTREXATE IN EARLY RHEUMATOID ARTHRITIS. (13th June 2020) - Fortea-Gordo, P.; Villalba, A.; Nuño, L.; Santos-Bornez, M. J.; Peiteado, D.; Monjo, I.; Puig-Kröger, A.; Sanchez-Mateos, P.; Martín-Mola, E.; Balsa, A.; Miranda-Carus, M. E.
Abstract : Background: The protagonism of regulatory B cells seems to vary along the course of the disease in murine models of inflammatory conditions. Decreased numbers of circulating regulatory CD19+CD24hiCD38hi transitional B cells (cTrB) have been described in patients with longstanding RA. Objectives: To examine the frequency and evolution of cTrB cells in the peripheral blood of early RA (ERA) patients. Methods: Freshly isolated PBMCs from 48 steroid and DMARD-naïve ERA patients with a disease duration below 24 weeks and 48 healthy controls (HC) were examined by flow cytometry. Cocultures of isolated memory B cells were established with autologous T cells, in the absence or presence of TrB cells. Results: As compared with HC, ERA patients demonstrated an increased frequency of cTrB cells. cTrBs of ERA and HC displayed an anti-inflammatory cytokine profile and were able to downregulate T cell IFNγ and IL-21 production, together with ACPA secretion in autologous B/T cell cocultures. Basal frequencies of cTrBs above the median value observed in HC were associated with a good EULAR response to MTX at 12 months (RR=2.91; 95% CI, 1.37-6.47). A significant reduction of cTrBs was observed 12 months after initiating MTX, when the cTrB cell frequency was no longer elevated but decreased, and this was independent of the degree of clinical response or the intake of prednisone. Conclusion: An increased frequency of regulatory cTrB cells is apparent in untreated ERA, and the baseline cTrB cell frequency is associated with the clinical response to MTX at 12 months. References: [1]Matsushita T, et al. J Clin Invest. 2008;118:342. Flores-Borja F, et al. Sci Transl Med. 2013;5:173ra23. Disclosure of Interests: Paula Fortea-Gordo Grant/research support from: BMS, Alejandro Villalba: None declared, Laura Nuño: None declared, Maria-Jose Santos-Bornez Grant/research support from: BMS, Diana Peiteado: None declared, Irene Monjo: None declared, Amaya Puig-Kröger: None declared, Paloma Sanchez-Mateos: None declared, Emilio Martín-Mola Grant/research support from: BMS, Roche, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz, Maria-Eugenia Miranda-Carus Grant/research support from: BMS, Roche